Entry modes in reshoring strategies: An empirical analysis. Issue 3 (June 2019) - Wan, Li; Orzes, Guido; Sartor, Marco; Di Mauro, Carmela; Nassimbeni, Guido
Abstract: The Entry Mode (EM) choice is a fundamental issue in reshoring initiatives. Despite several authors have studied the determinants of offshoring EM, no study has investigated so far the factors affecting the reshoring EM and its relation with the offshoring EM. The purpose of this paper is to examine which factors influence entry mode choice in reshoring initiatives. We develop a conceptual framework that explains the reshoring EM in terms of country-, industry-, firm- and project-specific factors, in addition to the offshoring EM choice. Next, we test this model by using a sample of 677 cross-industry and cross-country reshoring projects. Based on the results, we find that offshoring EM significantly constrains the subsequent reshoring EM. More in detail, firms adopting offshore insourcing entry modes tend to retain these modes in reshoring. Furthermore, reshoring EM is explained by industry- and project-specific factors, while offshoring EM is influenced by a broader set of industry-, country-, and firm-specific factors. This study fills a gap in the reshoring literature by analysing influential factors in EM choice and by offering a comparison between the determinants of offshoring and reshoring EM. Highlights: We shed light on the factors affecting the reshoring entry modes and their relationship with the offshoring entry modes. We show that reshoring entry mode choice is determined by both industry-level and project-level factors. Firms adopting offshore insourcing tend to keep the same entry modes in reshoring practices. Firms adopting offshore outsourcing may change entry modes towards insourcing in reshoring practices.